Baseline left atrial low-voltage area predicts recurrence after pulmonary vein isolation: WAVE-MAP AF results - Starek, Zdenek; Di Cori, Andrea; Betts, Timothy R; Clerici, Gael; Gras, Daniel; Lyan, Evgeny; Della Bella, Paolo; Li, Jingyun; Hack, Benjamin; Zitella Verbick, Laura; Sommer, Philipp (Europace, 2023)
AIMS: Electro-anatomical mapping may be critical to identify atrial fibrillation (AF) subjects who require substrate modification beyond pulmonary vein isolation (PVI). The objective was to determine correlations between pre-ablation mapping characteristics and 12-month outcomes after a single PVI-only catheter ablation of AF. METHODS AND RESULTS: This study enrolled paroxysmal AF (PAF), early persistent AF (PsAF; 7 days-3 months), and non-early PsAF (>3-12 months) subjects undergoing de novo PVI-only radiofrequency catheter ablation. Sinus rhythm (SR) and AF voltage maps were created with the Advisor HD Grid™ Mapping Catheter, Sensor Enabled™ for each subject, and the presence of low-voltage area (LVA) (low-voltage cutoffs: 0.1-1.5 mV) was investigated. Follow-up visits were at 3, 6, and 12 months, with a 24-h Holter monitor at 12 months. A Cox proportional hazards model identified associations between mapping data and 12-month recurrence after a single PVI procedure. The study enrolled 300 subjects (113 PAF, 86 early PsAF, and 101 non-early PsAF) at 18 centres. At 12 months, 75.5% of subjects were free from AF/atrial flutter (AFL)/atrial tachycardia (AT) recurrence. Univariate analysis found that arrhythmia recurrence did not correlate with AF diagnosis, but LVA was significantly correlated. Low-voltage area (<0.5 mV) >28% of the left atrium in SR [hazard ratio (HR): 4.82, 95% confidence interval (CI): 2.08-11.18; P = 0.0003] and >72% in AF (HR: 5.66, 95% CI: 2.34-13.69; P = 0.0001) was associated with a higher risk of AF/AFL/AT recurrence at 12 months. CONCLUSION: Larger extension of LVA was associated with an increased risk of arrhythmia recurrence. These subjects may benefit from substrate modification beyond PVI.
Keywords: výsledek terapie; Recurrence; Electroanatomic mapping; Pulmonary vein isolation; Heart Rate; srdeční frekvence; Catheter Ablation; flutter síní; recidiva; srdeční síně; Atrial Fibrillation; Pulmonary Veins; Treatment Outcome; Time Factors; lidé; Humans; časové faktory; Atrial Flutter; Electrophysiologic Techniques, Cardiac; venae pulmonales; elektrofyziologické techniky kardiologické; Atrial fibrillation; katetrizační ablace; Catheter ablation; Heart Atria; fibrilace síní; Low-voltage area